Interpretación de los cuidados de enfermería en el óbito fetal: una revisión sistemática - Cunalata Fajardo, Nathaly Jamileth (2025)
Introduction: Foetal death is a public health problem, affecting worldwide, with a rate of 13.9 foetal deaths per 1,000 births. In Ecuador, 1,438 foetal deaths were registered in 2022, representing an increase of 3.06% over 2021. This situation not only affects families, but also nurses. By investigating fetal death nursing care, nursing care is improved. Objective: To interpret the nursing care at foetal death by means of a literature review. Methodology: This is a descriptive qualitative research, based on the PRISMA statement and PICO method. Databases such as Medline, Scopus, Google Scholar, Dialnet and Scielo from 2018 were consulted. Results: The need for focused and humanised care that considers the psychological and spiritual dimensions of bereavement is highlighted. The importance of specific training in the management of perinatal bereavement and the development of competencies in relation to emotional care, as well as knowledge of applicable theories, is highlighted. In addition, the emotional impact on nursing is evidenced. Conclusion: The importance of strengthening the competencies of nursing staff in the care and emotional management of perinatal bereavement is revealed. Finally, it is essential to have protocols and models of care based on scientific evidence in order to provide better support and care to affected families. Keywords: nursing care, foetal death, nursing care, perinatal death.